The Influence of Use of Comic Media and Learning Motivation on Learning Outcomes in The Subject of Integrated Social Sciences Class Vii Primary School State 25 Takengon City - Rahmi Novalita, Rahmi Novalita; Kadarni, Kadarni; Muharramsyah, Rambang (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to describe; a) the influence of using comic media on learning outcomes in integrated Social Sciences subjects, b) the influence of learning motivation on learning outcomes in Integrated Social Sciences subjects, c) the influence of using comic media and learning motivation on student learning outcomes in Science subjects Integrated Social Knowledge. This type of research is experimental research using a quantitative approach. The subjects of this research were 22 students of Class VII of Takengon 25 State Junior High School. This research design uses One Group Pretest-Posttest Design. Data collection techniques use observation, questionnaires and documentation. Data analysis techniques include the t-test and anova test. The research results show that: a) there is a significant influence of the use of comic media on student learning outcomes, where the value of Sig. for the (partial) influence of there is a significant influence of learning motivation on student learning outcomes, where the Sig. for the (partial) influence of c) there is a significant influence of the use of comic media and learning motivation on student learning outcomes, where the value of Sig. for the (simultaneous) influence of X1 and X2) simultaneously on Learning Outcomes (Y).